Predicting the impact of anticipatory action on US stock market : an event study using ANFIS (a neural fuzzy model) - Mah, Ching Cheng (2008)
We adopt a Neuro-fuzzy (or Neural Fuzzy) model–Adaptive Neural Fuzzy Inference System (ANFIS)–to predict when the market would take positions in anticipating an event to occur (the action day), and how the market would react (point and direction predictions of price movement and trading activity) when the event occurs. With this information, an investor would be in a comparatively advantageous position to capture on the profitable opportunities.